Implementation of the PREMIER model based on river area to improve fourth-grade students’ mathematical problem-solving ability - Prihandoko, Yogi; Prastitasari, Herti; Kurahman, Taufik; Fendrik, Muhamad; Istianah, Tia Nur (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2023)
The problem in this study is the low ability to solve mathematical problems in geometry materials (square, rectangle, and triangle). An effort to overcome this problem is to conduct learning using the PREMIER model, which combines Project Based Learning, Realistic Mathematics Education, and Course Review Horay. This research uses a qualitative approach with the type of Classroom Action Research (CAR), carried out with four meetings. The subject of the study was a grade IV student of a public elementary school in Banjarmasin City in the academic year of 2021/2022, with a total of 13 students. The data analysis used is qualitative and quantitative. The results of this study show that student activity has increased, which at meeting one only reached 38.5% until at meeting four, it increased to 92.3% with a very active category.